Ground Surface Temperature History Since the Last Glacial Maximum in Northeast Asia: Reconstructions From the Borehole Geotherms of the International Continental Scientific Drilling Program. Issue 8 (25th April 2023) - Jiang, Guangzheng; Tian, Yuntao; Lv, Qingtian; Sandiford, Mike; Shi, Yizuo; Zou, Changchun; Ma, Feng; Deng, Chenglong; He, Lijuan; Hu, Shengbiao
Abstract: Past ground surface temperature (GST), one of the important aspects of paleoclimate reconstructions, can be inverted from borehole temperature measurements. Here, we report continuous 6, 100‐m temperature logs in the International Continental Scientific Drilling Program SK‐2e. We inverted the past GST changes from upper borehole temperature logging (<600 m). Below this depth, localized fluid flow masks the paleoclimate record. Inversions yield an approximately 2 K GST rise since 0.1–0.6 Kyr BP and an approximately 10 K rise since 20 Kyr BP. Assuming a ±5 K influence from the deep groundwater flow, the inverted temperature rise has varied between 8 and 12 K since 20 Kyr BP, which is consistent with previous reports since the Last Glacial Maximum. Our results emphasize the potential of borehole heat‐flow profiles as a record of climate changes and the importance of climate correction for heat‐flow determinations. Plain Language Summary: Temperatures within the shallow boreholes are perturbed by changes in ground surface temperature (GST) in response to paleoclimate variations and anthropogenic land use. The GST varies at different time scales, and these variations penetrate different depths underground. Thus, the borehole temperatures can be used for reconstructing the history of ground surface temperatures. Based on borehole geotherms of the International Continental Scientific Drilling Program in Northeast Asia, the past GST changes since the Last Glacial Maximum were inverted. The results show a ∼2 K surface temperature rise during 0.1–0.6 Kyr BP and a ∼10 K rise since 20 Kyr BP, which is consistent with previous independent estimates. Key Points: We report an undisturbed 6, 100‐m continuous heat‐flow profile from the scientific drilling project SK‐2e The heat‐flow profile recorded a 2 K rise of ground surface temperature in the last five centuries and a 10 K rise since the Last Glacial Maximum A basin‐scale comparison reveals localized heat‐flow anomalies induced by advective heat in deep and confined high‐permeability aquifers